STUDENT LEARNING ENGAGEMENT AMONG FIRST-SEMESTER STUDENTS: IMPLICATIONS FOR EDUCATIONAL MANAGEMENT - Alpendi Alpendi; Miftakhi Diah Rina; Trikinasih Handayani; Nur Rina Priyani Mirsa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning engagement is a key construct in higher education that plays a crucial role in determining the quality of learning processes and outcomes. For first-semester students, engagement is particularly critical as it relates to academic adaptation, motivation, and the development of self-regulated learning. In the context of teacher education, especially in Elementary School Teacher Education (PGSD), learning engagement is essential for shaping pedagogical and professional competencies of prospective teachers. However, studies integrating learning engagement with educational management perspectives remain limited. This study aims to analyze the level of learning engagement among first-semester students and examine its implications for educational management. A quantitative approach with a survey method was employed, involving all first-semester students of the PGSD program at Universitas Muhammadiyah Bangka Belitung in the 2025/2026 odd semester using total sampling. The instrument was a learning activity questionnaire covering six aspects: visual, oral, listening, writing, emotional, and mental activities, measured using a four-point Likert scale. Data were analyzed descriptively using mean scores and percentages. The results indicate that students’ learning engagement is generally in the “good” category, with an average score of 82.81%. The highest engagement was found in writing activities (86.38%), while the lowest was in oral activities (75.66%). These findings suggest that learning engagement is multidimensional but still dominated by receptive activities. Therefore, it is necessary to strengthen student-centered learning management effectively through discussions and project-based activities that can enhance student participation. In addition, learning evaluation should emphasize learning engagement rather than merely final outcomes so that learning engagement can be effectively improved. ABSTRAK Learning engagement merupakan konstruk kunci dalam pendidikan tinggi yang berperan penting dalam menentukan kualitas proses dan hasil pembelajaran. Pada mahasiswa semester pertama, learning engagement menjadi isu krusial karena berkaitan dengan kemampuan adaptasi akademik, motivasi, serta pengembangan self-regulated learning. Dalam konteks pendidikan guru, khususnya Program Studi Pendidikan Guru Sekolah Dasar (PGSD), learning engagement memiliki peran strategis dalam membentuk kompetensi pedagogik dan profesional calon guru. Namun, kajian yang mengaitkan learning engagement dengan perspektif manajemen pendidikan masih terbatas. Penelitian ini bertujuan untuk menganalisis tingkat learning engagement mahasiswa semester pertama serta implikasinya terhadap manajemen pendidikan. Penelitian menggunakan pendekatan kuantitatif dengan metode survei yang melibatkan seluruh mahasiswa semester pertama PGSD Universitas Muhammadiyah Bangka Belitung pada Semester Ganjil Tahun Akademik 2025/2026 melalui teknik total sampling sejumlah 242 mahasiswa. Instrumen penelitian berupa angket keaktifan belajar yang mencakup enam aspek, yaitu visual, lisan, mendengarkan, menulis, emosional, dan mental, dengan skala Likert empat tingkat. Data dianalisis secara deskriptif menggunakan nilai rata-rata dan persentase. Hasil penelitian menunjukkan bahwa learning engagement mahasiswa berada pada kategori baik sebesar 82,81%. Aspek tertinggi terdapat pada aktivitas menulis (86,38%) dan terendah pada aktivitas lisan (75,66%). Temuan ini menunjukkan bahwa learning engagement bersifat multidimensional, namun masih didominasi oleh aktivitas reseptif. Oleh karena itu, diperlukan penguatan pengelolaan pembelajaran yang berpusat pada mahasiswa melalui diskusi dan pembelajaran berbasis proyek yang mampu meningkatkan learning engagement, bukan sekadar aktivitas pembelajaran. Selain itu, evaluasi pembelajaran perlu menekankan proses keterlibatan mahasiswa, bukan hanya sekadar hasil akhir, agar learning engagement meningkat secara optimal.